Modern information retrieval - Baeza-Yates, R. (Ricardo); Ribeiro, Berthier de Ara?jo Neto, 1960- (New York : ACM Press ; Harlow, England : Addison-Wesley, c1999., 1999)
This is a rigorous and complete textbook for a first course on information retrieval from the computer science (as opposed to a user-centred) perspective. The advent of the Internet and the enormous increase in volume of electronically stored information generally has led to substantial work on IR from the computer science perspective - this book provides an up-to-date student oriented treatment of the subject.
1. Introduction -- 2. Modeling -- 3. Retrieval Evaluation -- 4. Query Languages (with Gonzalo Navarro) -- 5. Query Operations -- 6. Text and Multimedia Languages and Properties (with Nivio Ziviani) -- 7. Text Operations -- 8. Indexing and Searching (with Gonzalo Navarro) -- 9. Parallel and Distributed IR (Eric Brown) -- 10. User Interfaces and Visualization (Marti Hearst) -- 11. Multimedia IR: Models and Languages (Elisa Bertino, Barbara Catania and Elena Ferrari) -- 12. Multimedia IR: Indexing and Searching (Christos Faloutsos) -- 13. Searching The Web -- 14. Libraries and Bibliographical Systems (Edie Rasmussen) -- 15. Digital Libraries.Edward A Fox and Ohm Sornil)
Includes bibliographical references (p. 455-499) and index.
1
Keywords: Information storage and retrieval systems